2021
DOI: 10.1016/j.amjoto.2021.102996
|View full text |Cite
|
Sign up to set email alerts
|

Rised sudden sensorineural hearing loss during COVID-19 widespread

Abstract: Background Sudden sensorineural hearing loss (SSNHL) is commonly encountered in otolaryngologic practice. SARS-CoV-2 infection is typically marked by respiratory symptoms although neurologic manifestations of the disease have also been described. Objective We want to measure the incidence and clinical aspects of persons exhibiting in otolaryngology clinic (OC) with SSNHL during the COVID-19 widespread and in the constant interval of previous year. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 15 publications
4
45
0
6
Order By: Relevance
“…Data from an Italian audiology tertiary referral center showed that the incidence of SSNHL and combined acute cochlear-vestibular involvement was significantly higher during the COVID-19 pandemic than in previous periods, with a more severe clinical presentation of pure-tone audiometry (PTA) ( 17 ). A study from Turkey found an increased incidence of SSNHL during the COVID-19 epidemic, with 60.3% of subjects having signs compatible with COVID-19 ( 18 ). A large tertiary hospital in China also found an increase in SSNHL visits to the outpatient and emergency departments during the COVID-19 pandemic compared to the past ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…Data from an Italian audiology tertiary referral center showed that the incidence of SSNHL and combined acute cochlear-vestibular involvement was significantly higher during the COVID-19 pandemic than in previous periods, with a more severe clinical presentation of pure-tone audiometry (PTA) ( 17 ). A study from Turkey found an increased incidence of SSNHL during the COVID-19 epidemic, with 60.3% of subjects having signs compatible with COVID-19 ( 18 ). A large tertiary hospital in China also found an increase in SSNHL visits to the outpatient and emergency departments during the COVID-19 pandemic compared to the past ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the ratio of diagnosis over the total patients evaluated was not very different between the two periods (1.91% vs 1.77%). Conversely, Fidan et al [14] , analysing a wider period (April 1st to September 30th 2020 versus 2019), reported an increased incidence of SSNHL during the COVID-19 pandemic. Notably, 57.4% of their patients tested positive for SARS-CoV-2 with nasopharyngeal swabs, strengthening the relationship between SSNHL and SARS-CoV-2 infection [15] , [16] .…”
Section: Discussionmentioning
confidence: 94%
“…Although more evidence is yet to be found, the temporal relation between the AZCV exposure and the appearance of hearing loss and tinnitus a few days after the vaccination in all cases clearly points toward a likely association between the vaccine and the otologic symptoms. Many authors have considered a possible link between COVID-19 infection and SSHL [2,[6][7][8][9][10]; however, as far as the author knows this is the first case series considering the possible association between a COVID-19 vaccine and inner ear damage, which could indeed have pathophysiology similar to that of the cases of SSHN secondary to COVID-19 infection. We display the audiometries of cases 1 and 5 since we believe them to be the most representative of the situation described by Tseng et al [12] (case 1) and the one described by Tsetsos et al [11] (case 5).…”
Section: Discussionmentioning
confidence: 97%
“…Several previous reports have mentioned the possible link between COVID-19 infection and inner ear damage [2,[6][7][8][9][10]; however to the authors´ very best knowledge this is the first case series considering the possible association between AZCV (or any COVID-19 vaccine) and inner ear damage, and so far only two previous isolated single case reports of auditory symptoms related to the AZCV have been described, including one report of SSHL itself [11], and one report of tinnitus presumably associated to cochleopathy secondary to the vaccine [12]. To our best knowledge, this is the first report of a patient with vestibular symptoms related to the AZCV.…”
Section: Introductionmentioning
confidence: 99%